COVID-19 vaccine hesitancy in Malaysia: Challenges within the law and way forward - Hafidz Hakimi, Haron; Nadiah, Arsat; Muhammad Ashraf, Fauzi (International Islamic University Malaysia, 2023)
For hundreds of years, vaccines have been a critical tool in the prevention of viral diseases. Vaccination programmes have gained prominence as one of the primary strategies for combating the COVID-19 pandemic. Despite this, COVID-19 vaccination programmes have frequently been viewed negatively by many. This is evident by the fact that vaccine hesitancy continues to grow at an unprecedented rate which is much facilitated by the rapid growth of communication and information technology. Despite the fact that vaccines and vaccinations are considered medical products, the difficulties they present are socio-legal in nature. The study examines four major factors that contribute to COVID-19 vaccine hesitancy in Malaysia namely compulsory vaccination and adverse event following vaccination (AEFI), information disclosure, misleading religious beliefs and sentiments, and misinformation and disinformation. It should be noted that, the identification and discussion of the factors mentioned above are vital as the failure of any future vaccination campaigns resulting from vaccine hesitancy would pose a huge threat to achieve the United Nations' Sustainable Goals (UNSDG), especially in respect of good health and sustainable economic growth. Therefore, for the purpose of this research, the paper adopts qualitative research approach to achieve its objectives. The paper recommends that the Malaysian vaccination legal framework be strengthened.